Judicial Reasoning Under the UK Human Rights ACT - Fenwick, Helen (Cambridge University Press, 2013)
A number of commentators have pointed out that the inception of Bills of Rights tends to have the effect, as in Canada, of requiring courts to grapple with justifications for rights and freedoms, taking a more philosophical approach to legal reasoning as they attempt to resolve conflicts between individual rights and competing societal and individual interests.1 When countries adopt a document setting out a list of human rights with special constitutional status (‘a Bill of Rights’), the effect on judicial reasoning tends to be dramatic – as it was in Canada when it adopted the Charter of Rights. In 2000, the Human Rights Act came into force – affording the European Convention on Human Rights further effect in domestic law – and, while it does not have the entrenched status of other Bills of Rights, there is agreement that it does have what ‘constitutional’ status UK law allows.2